Sport, exercise and health in the age of Corona - Tucker, R.; Finch, M. (The Real Science of Sport Podcast, 2020)
The impact of the Coronavirus across the globe has been felt in every sphere of life, including sport. From the cancellation and postponement of most major sporting events, including the Olympic Games, to the future of the professional game, Covid19 is likely to have a lasting effect. Join Prof. Ross Tucker and host Mike Finch as they discuss the impact of the pandemic, how and when normal sport may resume, the consequences of reduced training time and the role health and fitness play in the fight against the virus.